2021
DOI: 10.1007/s00239-021-10008-2
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Severe Acute Respiratory Syndrome Coronavirus-2 during Pandemic and Adaptation to the Host

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 is a zoonotic virus with a possible origin in bats and potential transmission to humans through an intermediate host. When zoonotic viruses jump to a new host, they undergo both mutational and natural selective pressures that result in non-synonymous and synonymous adaptive changes, necessary for efficient replication and rapid spread of diseases in new host species. The nucleotide composition and codon usage pattern of SARS-CoV-2 indicate the presence of a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 82 publications
3
14
0
Order By: Relevance
“…approximately 30 SNPs per genome) were observed for the most distant SARS-CoV-2 2021 isolates. This indicated that it should be possible to analyze the time dependence of codon usage frequencies for SARS-CoV-2 ORFs, although only a small variation was expected, as it was previously observed by Hussain et al (2021) and Huang et al (2021) . These authors conducted similar time-series analysis, principally of averaged ENC and CAI values, showing that in the first months of COVID-19 pandemic both indices were slowly decreasing.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…approximately 30 SNPs per genome) were observed for the most distant SARS-CoV-2 2021 isolates. This indicated that it should be possible to analyze the time dependence of codon usage frequencies for SARS-CoV-2 ORFs, although only a small variation was expected, as it was previously observed by Hussain et al (2021) and Huang et al (2021) . These authors conducted similar time-series analysis, principally of averaged ENC and CAI values, showing that in the first months of COVID-19 pandemic both indices were slowly decreasing.…”
Section: Discussionsupporting
confidence: 53%
“…The main codons contributing to differences in SARS-CoV-2 variants were AAA-Lys (A < D/G < B), AAG-Lys (B < G/D < A), ACA-Thr (D < A/B/<G), ACC (B/G < A/D), ACG (A/B < D/G), AGG (G < D < A < B), CCA (G < D < B < A), CCC (A < B < D < G), CCG (A < B/D < G), CGA (D/B < A < G), CGG (B/G/A < D), CTG (D < G/B/A), GAA (ABGD <average), GAG (ABDG >average), GCA (BDG < A), GTG (ABD < G), TAC (G < D/B < A), TAT (A < B/D < G), TCC (A < G < B/D), TGC (A/D < G/B), TGT (G/D < A/B), and TTG (ABGD <average). Interestingly, some of the codons which presented an increase in the ACUF (although slight) contained CG or TA dinucleotides (ATA, ATT, CAT, GCG, and CGA), and it was speculated that an increase of CpG and UpA dinucleotides could reduce SARS-CoV-2 pathogenicity ( Hussain et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations